34. THE CORRELATION BETWEEN ULTRASOUND IMAGES AND CYTOLOGY OF SMALL THYROID NODULES AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Introduction: Ultrasound of the thyroid is becoming increasingly common, aiding in the detection of small thyroid nodules. The indication for fine-needle aspiration (FNA) in small thyroid nodules remains a topic of much debate. However, early detection of malignant small thyroid nodules is crucial for appropriate management.Methods: This cross-sectional descriptive study involved patients with thyroid nodules who underwent ultrasound and FNA at Thong Nhat Hospital in 2023. Ultrasound evaluations were categorized using the TIRADS system, while thyroid cytology was classified based on the 2023 Bethesda system.Results: The study included 827 patients with 1173 thyroid nodules, who underwent both ultrasound and FNA at Thong Nhat Hospital. Among the nodules classified as TIRADS 4 and 5, most had cytological diagnoses in Bethesda categories I, II, and III, with 164 cases (26.2%), and only 46 cases (7.4%) fell into categories IV, V, and VI. The TIRADS classification was significantly correlated with the Bethesda cytological classification for benign small thyroid nodules.Conclusion: There is a relationship between ultrasound images and cytology of small thyroid nodules, the most obvious association is thyroid nodules in TIRADS groups 1, 2, 3 (group with little suspicion of malignancy) with cytological aspiration results in the TIRADS group. II according to Bethesda (group with low risk of malignancy).Recommendation: FNA should be performed for small thyroid nodules with malignant potential based on ultrasound assessment. Especially thyroid nodules larger than 5 mm in size. In addition, consider monitoring and re-doing FNA for patients when indicated to avoid missing cases of malignant thyroid nodules.
Keywords: Thyroid ultrasound; TIRADS; FNA; small nodule